The validity of the Fisher effect for an inflation targeting country : the case of Turkey - Gürel, Sinem Pınar (Array, 2021)
The aim of this paper is to investigate the relationship between interest and inflation rates. In this regard, the validity of the Fisher Effect under an inflation targeting regime country is examined by considering the possibility of non-linearities. To this aim, the Fisher Effect is analysed by using various types of interest rates to identify the short-, mid- and long-term dynamics. Autoregressive distributed lag (ARDL) and non-linear autoregressive distributed lag (NARDL) models were estimated for Turkish economy between 2006-2019 periods. The empirical findings of ARDL models reveal the validity of Fisher Effect both for short and long run. The results of NARDL models indicate a strong Fisher Effect in the long run, except for 5-year government bonds. For short-run, the Fisher Effect holds only when inflation rises and there is no significant result when inflation decreases.